1969
DOI: 10.2135/cropsci1969.0011183x000900030014x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations Among Agronomic Characters in Grain Sorghum (Sorghum bicolor Moench)1

Abstract: Genotypic and phenotypic correlations among 12 characters were estimated in segregating populations and in pure lines of grain sorghum (Sorghum bicolor Moench). Grain yield was positively and significantly correlated with head weight, kernel number, half bloom date, and leaf number, but negatively correlated with germination percentage and protein percentage. The inverse relationships between kernel weight and kernel number, and between kernel weight and head number per plant may arise from developmentally ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
7
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
6
7
0
Order By: Relevance
“…Plant height, stay green and maturity are all associated with grain yield in Australian sorghum growing environments. The strong correlation (r = 0.47) we observed between increased plant height and grain yield in this study is often noted in sorghum (Casady 1965;Graham and Lessman 1966;Liang et al 1969;Henzell et al 1982). The variation in plant height among the genotypes in this study was not extreme, with all hybrids being of acceptable height for commercial production.…”
Section: Discussionsupporting
confidence: 69%
“…Plant height, stay green and maturity are all associated with grain yield in Australian sorghum growing environments. The strong correlation (r = 0.47) we observed between increased plant height and grain yield in this study is often noted in sorghum (Casady 1965;Graham and Lessman 1966;Liang et al 1969;Henzell et al 1982). The variation in plant height among the genotypes in this study was not extreme, with all hybrids being of acceptable height for commercial production.…”
Section: Discussionsupporting
confidence: 69%
“…Jordan et al (2003) investigated the performance of sorghum hybrids and found a strong correlation between increased plant height and grain yield. This correlation has been previously observed in sorghum (Graham and Lessman, 1966;Liang et al, 1969).…”
Section: Physiological Responses Of Sorghum To Water Deficit At Reprosupporting
confidence: 88%
“…, Basu (1971), Khanure (1993), Reddy et al (1996) Liang et al (1969), Chung and Liang (1970), Basu (1971), Phul et al (1972), Naphade (1973), Singh and Singh (1973), Bhat (1975), Eckebil et al (1977), Dhimer and Desai (1978), Pauli (1980), Makne (1980), Nagabasaih (1981), Kukadia et al (1983), Bello and Obilana (1985), Phul and Allah Rang (1986), Worthman et al (1987), Khanure (1993), Reddy et al (1996) Basu (1971, Phul et al (1972), Bhat (1975), Reddy et al (1996) Plant height Krantikumar et al (1970), Basu (1971), Naphade and Ailwar (1977), Singh and Makne (1980), Patel et al (1980b), Berenji (1990) Naphade (1973), Singh and Singh (1973), Shinde and Nayeem (1979), Singh and Makne (1980), Salilkumar and Singhania (1984), Kumar and Singh (1986), Worthman et al (1987), Rao and Patil (1996), Biradar et al (1996a,b), Nguyen et al (1999) Basu (1971), …”
mentioning
confidence: 99%
“…Univariate analysis: Voluminous literature is available on this subject, and it is evident from the literature that a vast reservoir of variability exists for several traits of interest in sorghum. A few studies have reported low genetic variability (Lonc, 1969; Naphade and Ailwar, 1977;Patel et al, 1980;Raja and Parikh, 1980;Berenji, 1990;Wenzell et al, 1998), low heritability (Ciobanu, 1968;Liang and Walter, 1968;Liang et al, 1969;Fanous et al, 1971;Singh and Singh, 1973;Jan-Orn, 1974;Miller, 1975;Rao and Goud, 1979;Kanaka and Goud, 1982;Obilana and Okoh, 1984;Kulkarni and Shinde, 1987), and low level of genetic advance (Fanous et al, 1971;Naphade, 1973;Singh and Singh, 1973;Patel et al, 1980b;Khanure, 1993). This serves as a raw material for the genetic enhancement/prebreeding of winter sorghum and the development of varieties and hybrids.…”
mentioning
confidence: 99%